Efficacy and Safety of Phikud Tri-Phon Herbal Decoction for Weight Management in Young Adult Thai Females: A Double-Blind, Randomized Controlled Trial - Naparat Doungchan; Marisa Poomiphak Na Nongkhai; Sulukkana Noiprasert; Rajesh Kumar; Ngamrayu Ngamdokmai (International Journal of Environmental Research and Public Health, 2026)
Overweight and obesity are concerns among young adults. This double-blind, randomized, placebo-controlled trial evaluated the efficacy and safety of Phikud Tri-Phon (PTP), a traditional Thai herbal decoction comprising Aegle marmelos, Morinda citrifolia, and Coriandrum sativum, for weight management in Thai females. Forty females aged 18–22 years with a body mass index (BMI) of 23.0–24.9 kg/m2 were randomly assigned to receive 150 mL of PTP decoction or a herbal-style placebo control twice daily for 6 weeks. Body composition, obesity-related indices, lipid profiles, and kidney and liver function markers were assessed at baseline and after the intervention. Per-protocol analyses included 17 participants in the PTP group and 16 in the placebo group. No statistically significant between-group differences were observed in body composition, obesity-related indices, lipid profiles, or kidney and liver biochemical markers after 6 weeks (p > 0.05). Although a device-derived metric of obesity degree decreased within the PTP group (p = 0.021), this change did not differ significantly from that of the placebo group (p = 0.894). No clinically meaningful between-group safety differences were identified during the 6-week study period.